HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG KESEHATAN REPRODUKSI DENGAN PERILAKU SEKS PRANIKAH PADA REMAJA USIA (15-17 TAHUN) DI SMK YADIKA 13 TAMBUN, BEKASI - Aritonang, Tetty Rina (Jurnal Ilmiah Widya, 2015)
Reproductive health is one of the problems that occur in teenagers today. It is necessary for them to understand of: (1) the maintenance of hygiene tool reproductions, (2) reproductive processes and (3) the impact of irresponsible behavior such as unwanted pregnancy, abortion, and sexually transmitted diseases. The purpose of this research is to know the relation of knowledge and attitudes about reproductive health with premarital sex behaviors. The sample used as many as 105 people i.e. teen age (15-17 years). The method used is descriptive analytic with cross sectional approach. The data analyzed in Univariate and bivariat with Chi-Square test using SPSS 16. The results showed that: (1) there is a significant relationship between knowledge and attitudes about reproductive health with premarital sex behaviors in adolescent age (15-17 years), (2) knowledge and good attitude will affect the behavior of premarital sex. (3) knowledge and attitudes are predisposing factors inside a person which motivate to act either positive or negative action